Streptomyces natalensis programmed cell death and morphological differentiation are dependenton oxidative stress - Beites, T (2015)
Streptomyces are aerobic Gram-positive bacteria characterized by a complex life cycle that includes hyphae differentiation and spore formation. Morphological differentiation is triggered by stressful conditions and takes place in a pro-oxidant environment, which sets the basis for an involvement of the oxidative stress response in this cellular process. Characterization of the phenotypic traits of Streptomycesnatalensis ΔkatA1 (mono-functional catalase) and ΔcatR (Fur-like repressor of katA1 expression) strains in solid medium revealed that both mutants had an impaired morphological development process. The sub-lethal oxidative stress caused by the absence of KatA1 resulted in the formation of a highly proliferative and undifferentiated vegetative mycelium, whereas de-repression of CatR regulon, from which KatA1 is the only known representative, resulted in the formation of scarce aerial mycelium. Both mutant strains had the transcription of genes associated with aerial mycelium formation and biosynthesis of the hyphae hydrophobic layer down-regulated. The first round of the programmed cell death (PCD) was inhibited in both strains which caused the prevalence of the transient primary mycelium (MI) over secondary mycelium (MII). Our data shows that the first round of PCD and morphological differentiation in S. natalensis is dependent on oxidative stress in the right amount at the right time.